Adaptive multi‐degree‐of‐freedom in situ bioprinting robot for hair‐follicle‐inclusive skin repair: A preliminary study conducted in mice - Wenxiang Zhao; Haiyan Chen; Yi Zhang; Dezhi Zhou; Lun Liang; Boxun Liu; Tao Xu (Wiley, 2022)
Abstract Skin acts as an essential barrier, protecting organisms from their environment. For skin trauma caused by accidental injuries, rapid healing, personalization, and functionality are vital requirements in clinical, which are the bottlenecks hindering the translation of skin repair from benchside to bedside. Herein, we described a novel design and a proof‐of‐concept demonstration of an adaptive bioprinting robot to proceed rapid in situ bioprinting on a full‐thickness excisional wound in mice. The three‐dimensional (3D) scanning and closed‐loop visual system integrated in the robot and the multi‐degree‐of‐freedom mechanism provide immediate, precise, and complete wound coverage through stereotactic bioprinting, which hits the key requirements of rapid‐healing and personalization in skin repair. Combined with the robot, epidermal stem cells and skin‐derived precursors isolated from neonatal mice mixed with Matrigel were directly printed into the injured area to replicate the skin structure. Excisional wounds after bioprinting showed complete wound healing and functional skin tissue regeneration that closely resembling native skin, including epidermis, dermis, blood vessels, hair follicles and sebaceous glands etc. This study provides an effective strategy for skin repair through the combination of the novel robot and a bioactive bioink, and has a promising clinical translational potential for further applications.